Effect of Zoom-Assisted Learning Media on Physics Concept Understanding at MAN Pinrang - Idris*, Ihfa Indira Nurnaifah; Sanusi, Dirgah Kaso (Journal of Physics Education : Review and Research, 2025)
The advancement of information technology has significantly transformed the education landscape, particularly in facilitating distance learning. Applications like Zoom have enabled real-time interaction between teachers and students, regardless of their physical location. This shift became especially prominent during the COVID-19 pandemic, which accelerated the adoption of digital platforms in education. Zoom-based learning offers a flexible, interactive, and student-centered environment. However, the effectiveness of such media in enhancing conceptual understanding—especially in abstract subjects like physics—remains a key question. Preliminary observations at MAN Pinrang revealed that Zoom is already used as a learning tool, but its actual impact on students’ conceptual understanding is still unclear. Therefore, this study aims to investigate the effect of Zoom-assisted learning media on students’ understanding of physics concepts. A quantitative approach with an ex post facto design was applied. The sample consisted of 70 students from class XII MIPA 2 and XII MIPA 3 at MAN Pinrang, selected using purposive sampling. Data were collected through questionnaires, observation, and documentation. The findings show that Zoom-based media supports interactive learning, promotes student independence, and has a statistically significant influence on physics concept comprehension, although the effect size is categorized as small (value 0.101 > 0.025).